The G. Stanley Hall Lecture Series, Vol. 8. 1988
DOI: 10.1037/10062-004
|View full text |Cite
|
Sign up to set email alerts
|

Increasing awareness of class, ethnicity, culture, and race by expanding on students' own experiences.

Abstract: BRlSLlNcepts is demonstrated by showing how they relate to such important topics as education, health, interpersonal relations, and child rearing practices.Of course, social class, ethnicity, culture, and race do not exhaust the major concepts summarizing influences on human diversity. Others have been reviewed in previously published G. Stanley Hall collections: age (Kagan, 1985;Schlossberg, 1984); sex (Denmark, 1983); psychological abnormalities (Sarason, 1983); and the physical environment in which people f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Trainees also explore the values of their family of origin, their present family, their life experiences with different cultures, and their theoretical slants in the same four basic parameters. Awareness of class, ethnicity, and religion are increased by focusing on the trainees’ own experiences (Brislin, 1988).…”
Section: Comparing Cultural Mapsmentioning
confidence: 99%
“…Trainees also explore the values of their family of origin, their present family, their life experiences with different cultures, and their theoretical slants in the same four basic parameters. Awareness of class, ethnicity, and religion are increased by focusing on the trainees’ own experiences (Brislin, 1988).…”
Section: Comparing Cultural Mapsmentioning
confidence: 99%
“…In l ggGl 9g l, the percentage of renured ethnic minority faculry in doctoral departments was 3.tgo, i,ith 5o.z% of the ethnic minoriry in faculty positircns being tenured, 4Z.gVo in tenure-wack positions, and 7% in non-tenure-track positions (Russo, Olmedo, Stapp, & Fulcher, 1981). In 1988, Kohout et al, (1991 found that 4% of the tenured faculty were members of an ethnic minority, with 38% in tenure-track positions and 1306 in non-tenure-track positions. Although there was an increase after 9 years in the percentage of tenured ethnic minority faculty, a larger percentage of the ethnic minority faculty were found to be in non-tenure-track positions.…”
Section: Ethnic Minorities and Academic Psychology Studenrsmentioning
confidence: 98%
“…In 1980, 11.8% of the psychology graduate students were members of an ethnic minority. By 1988, in. p.r..rrt"ge had remained relatively sratic at 11.3% (Kohout & Pion, 1990; Pion et al, 1989).…”
Section: Ethnic Minorities and Academic Psychology Studenrsmentioning
confidence: 99%
“…Certainly, there is no acknowledgement of culture within the Australian Psychological Society's guidelines for course accreditation or evidence that university curricula and professional psychological services on the whole acknowledge that the needs of persons from different ethnic and cultural backgrounds may differ from those of the cultural mainstream. In our Australian journals there is no debate about issues like what factors affect the outcome of cross-cultural interventions or how race of counsellor and client affect therapeutic outcomes as there is elsewhere (e.g., Brislin, 1988;Sue, 1988;Sue & Sue, 1990).…”
Section: Graham Davidsonmentioning
confidence: 99%